Incentive mechanism for sharing distributed energy resources - Jianxiao Wang; Haiwang Zhong; Junjie Qin; Wenyuan Tang; Ram Rajagopal; Qing Xia; Chongqing Kang (Journal of Modern Power Systems and Clean Energy, 2019)
To improve the controllability and utilization of distributed energy resources (DERs), distribution-level electricity markets based on consumers' bids and offers have been proposed. However, the transaction costs will dramatically increase with the rapid development of DERs. Therefore, in this paper, we develop an energy sharing scheme that allows users to share DERs with neighbors, and design a novel incentive mechanism for benefit allocation without users' bidding on electricity prices. In the energy sharing scheme, an aggregator organizes a number of electricity users, and trades with the connected power grid. The aggregator is aimed at minimizing the total costs by matching the surplus energy from DERs and electrical loads. A novel index, termed as sharing contribution rate (SCR), is presented to evaluate different users' contributions to the energy sharing. Then, based on users' SCRs, an efficient benefit allocation mechanism is implemented to determine the aggregator's payments to users that incentivize their participation in energy sharing. To avoid users' bidding, we propose a decentralized framework for the energy sharing and incentive mechanism. Case studies based on real-world datasets demonstrate that the aggregator and users can benefit from the energy sharing scheme, and the incentive mechanism allocates the benefits according to users' contributions.